The Relationship between the Characteristics of the Village Midwives and the Geographical Location of the Village Maternity Post (POLINDES) with the Quality of Antenatal Care Services in Southwest Sumba Regency - Conchita Emiliana Ndapa, Diadjeng Setya Wardani, Dan Sutrisno, (Pakistan Journal of Medical & Health Sciences, 2022)
One of the provinces that have had a rise in MMR since 2019 is East Nusa Tenggara (NTT) Province. Southwest Sumba Regency saw an upsurge in maternal mortality cases in 2019, with ten cases; in 2020, there were nine cases; and as of October 2021, there were 14 MMR mothers. Having better antenatal care is one of the crucial measures to lower MMR and IMR. In order to perform their duties in accordance with the established standard operating procedures, midwives must be as prepared as feasible. One of them is raising the bar on several aspects of service quality, such as technical proficiency, service accessibility, effectiveness, efficiency, continuity, security, convenience, information, timeliness, and interpersonal relationships. This study has a cross-sectional design and is an analytical observational study. Using inclusion and exclusion criteria, a sample of 120 respondents was selected using the cluster random sampling technique. The information was gathered through the distribution of a questionnaire about midwives' knowledge of common antenatal care (ANC) examination services and the completion of a checklist to investigate the aspects of midwifery service quality and patient comfort during ANC visits. Chi-square analysis was used to examine the data. On the traits of the village midwives, the chi-square test and correlation test findings were obtained. Knowledge was the impacting factor (p-value 0.000; r = 0.599). With ANC visits, Polindes' distance from the houses of pregnant women had a p-value of 0.001 (r= 0.293). The p-value for the distance between Polindes and the residences of expectant women having quality ANC service is 0.027 (r=0.202). A p-value of 0.004 (r= 0.265) was obtained for the outcomes of the ANC visit test and the quality of ANC services. Knowledge and the geographic location of Polindes are the features of village midwives associated with the quality of ANC services in Southwest Sumba Regency.